2020
DOI: 10.20527/jps.v7i1.8074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Antibiotics on Patients Surgery, before and after Used Guidelines for Antibiotics (PPAB)

Abstract: ABSTRAK Sejak    tahun    2011    World   Health    Organisasi   (WHO)   dan    Komite Pengedalian Resisten Antimikroba  (KPRA) sejak 2015, untuk  menetapkan kebijakan penggunaan antibiotik  dengan menyusun formularium dan  Pedoman Penggunaan Antibiotik (PPAB). Penggunaan antibiotik  berlebihan berkontribusi pada resistensi maka  penelitian ini bertujuan, menganalisis besarnya perbedaan penggunaan antibiotik  pada pasien rawat  inap bedah sebelum digunakan PPAB (Periode  Mei 2018)  dan  setelah  digunakan  PPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…There were 13 reports that reported data on the effect of AMS interventions in hospitals (11 reports), 24 , 27 , 33 , 46 , 85 , 86 , 87 , 88 , 89 , 90 , 91 primary care (1), 92 and community pharmacies (1) 93 ( Table 2 ). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%
“…There were 13 reports that reported data on the effect of AMS interventions in hospitals (11 reports), 24 , 27 , 33 , 46 , 85 , 86 , 87 , 88 , 89 , 90 , 91 primary care (1), 92 and community pharmacies (1) 93 ( Table 2 ). Twelve reports used a pre-post design, and one was a randomized controlled trial.…”
Section: Resultsmentioning
confidence: 99%
“…Studies that evaluated the implementation of antibiotic prescribing guidelines or clinical pathway (7 reports) reported mixed effects on antibiotic consumption and favourable effects on prescribing appropriateness. 23, 31, 47, 86, 88, 90, 91 Studies that evaluated education and/or training interventions (5 reports) reported mixed effects on antibiotic consumption and prescribing appropriateness. 31, 87–89, 92…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 reports (5 193 626 patients) reported data on antibiotic consumption. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Most of the studies were conducted in hospital settings (16 reports, 76.2%), in Java (14 reports, 66.7%), and between 2016-2021 (17 reports, 81.0%; Table S4). The pooled estimate of overall antibiotic…”
Section: Antibiotic Consumptionmentioning
confidence: 99%
See 2 more Smart Citations